AI DRIVEN ISLAMIC BUY NOW PAY LATER (BNPL) – A LEGAL ANALYSIS - Klemens Katterbauer; Hassan Syed; Sema Yilmaz Genc; Laurent Cleenewerck (Journal of Management and Islamic Finance, 2023)
Buy Now Pay Later (BNPL) schemes have experienced worldwide rapid growth rates in order to stimulate consumption growth and provide consumers with more options in paying for their items. Traditional consumers were offered for a long time offers where they may purchase products and services and then pay them off over a period of time. BNPL schemes are a new form of electronic installment payment arrangements that permit the purchase of even smaller items and pay them off over a period of time. While installment options were mostly restricted to larger purchases, such as cars and furniture, newer BNPL enable to purchase efficiently even less expensive goods and services. This change in opportunities has attracted merchants and financial services provider in Islamic countries to evaluate BNPL for their business and provide it to their consumers. Islamic law has various forms of contracts that may be utilized for BNPL scheme. However, the most common form is the structure of a Murabaha for financing these schemes. The article outlines the general BNPL structure for Islamic finance and the legal issues that arise from general BNPL schemes. Ensuring the solid connection between goods and services and the financing is paramount for maintaining compliance with Shariah law. The legal analysis outlined several structures that are suitable for BNPL schemes that are Shariah compliant, enabling Islamic finance to strengthen the sector and provide dedicated financing options.